Desenvolvimento de uma barra de cereais fonte de fitoestrogênios e efeitos na sintomatologia de mulheres climatéricas - Frigo, Maiara (2019)
Climacteric occurs between 40 and 65 years of age in women, where there is a decline in the production of ovarian hormones, estrogen and progesterone. It may occur symptomatically or asymptomatically, varying the intensity and diversity of symptoms, but affecting the quality of life. As an alternative and natural therapy to alleviate these symptoms, phytoestrogens (EF) have been studied. The aim of this study was to evaluate the effects of the consumption of a cereal source bar of EF by climacteric women in relation to the clinical, nutritional parameters and climacteric symptoms. This was a prospective randomized controlled clinical study involving 46 women, divided into intervention and control groups. The development, physicochemical characterization, sensorial and microbiological analysis of a source bar of EF were carried out. The intervention group received for 90 days a cereal bar containing 80.73 mg of FE and the placebo group received an expanded brown rice flake biscuit that did not contain any ingredient that could intervene in climacteric symptoms. Clinical, anthropometric, biochemical and hormonal profile data were collected. Climacteric symptoms were assessed using the Kupperman Menopausal Index (IK). These variables were evaluated at time 0 and after 90 days. Statistical analysis was performed using descriptive statistics, Student's t-test and Pearson's chi-square. At the end of the intervention, there was a reduction in climacteric symptoms assessed by IK, a significant increase in HDL cholesterol and a reduction in LDL cholesterol in both groups. Increased plasma estradiol levels were observed in the intervention group and a reduction in FSH levels in the control group. It was concluded that the source bar of developed EF presented satisfactory physicochemical composition, good microbiological standards and good sensory acceptability. Improvement in climacteric symptoms and positive changes in the biochemical and hormonal profile were observed after 90 days of intervention, which were also observed in the placebo group, except for the increase in estradiol that was observed only in the intervention group.